2014
DOI: 10.1108/meq-01-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different methods of treatment for an integrated municipal waste management for an Algerian city

Abstract: Purpose – The purpose of this paper is to provide suitable solutions to the management system of the municipal solid waste in an Algerian city. Design/methodology/approach – The adopted approach focussed on the evaluation of different methods concerning the Municipal Solid Waste Management (MSWM), by analyzing methods of solid waste management hierarchy which constitutes appropriate tools in the MSWM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Analysis of the remaining parameters showed significant index for "thermal environment", "noise", "time pressure" and "working hours". These parameters can present serious risks to the health and must be managed [16].…”
Section: Discussion and Interpretation Of The Resultsmentioning
confidence: 99%
“…Analysis of the remaining parameters showed significant index for "thermal environment", "noise", "time pressure" and "working hours". These parameters can present serious risks to the health and must be managed [16].…”
Section: Discussion and Interpretation Of The Resultsmentioning
confidence: 99%
“…In Batna city, Algeria, the suitable treatment for the MSW of Batna is recycling. It is found that the MSW of Batna city Integrated Municipal Solid Waste Management was given, as shown in Figure 1 (Sefouhi, Kalla, & Bahmed, 2014).…”
Section: Improving Local Economy Through Integrated Waste Management…mentioning
confidence: 93%
“…Dry leaves, paper, food scraps, plastic, and glass are the common examples. The regional solid waste management system must include basic strategic steps, such as recycling, biological treatment, thermal treatment, and landfilling; however, these strategic steps are insufficient to ensure efficient and sustainable management [9]. Some of the challenges in the waste management system include inadequate waste collection and storage, lack of landfills, waste recovery and treatment systems, as well as poor public awareness to reduce and separate solid waste [10].…”
Section: Introductionmentioning
confidence: 99%